Optimalisasi Manajemen Produksi Dan Pemasaran Tahu Dan Tempe Di Lingkungan Industri Kecil Menengah - Septi, Septi; Meytha, Ida Made Ayu Er; Wagini, Wagini; Mulyana, Andy; Kamelia, Kamelia (Jurnal Dehasen Mengabdi, 2024)
This community service activity aims to optimize production and marketing management of tofu and tempeh in the Small and Medium Industry (IKM) environment. The main focus of this program is to increase the efficiency of the production process and expand the marketing reach of products through technology and digital marketing strategies. The methods used are surveys and observations, technical assistance and monitoring and evaluation. In the production aspect, the main challenge is raw materials whose prices are starting to rise or become expensive, while in the marketing aspect the challenge faced is competition between other factories.